LOS BIENES PÚBLICOS URBANOS Y LA REGULACIÓN URBANÍSTICA COLOMBIANA (2016)
Urban public goods are those which transform rural land in urban land, enabling a more intensive land use, this occur because of their existence and their distribution along the city make the spaces accessible and livable, increasing its density. This is the reason why cities become centers of social and economic development by allowing the concentration of different economic activities and cultural.Ensuring universal provision of urban public goods is a State obligation ordered by the Political Constitution, because having urban public goods in quantities and optimal conditions allow citizens to exercise effectively theirs “right to the city”. The existing legal instruments for achieving the social objectives of the State are abundant and full of good intentions, but their effectiveness is questioned, because today a large numbers of people in the cities are excluded from enjoying of these goods, which are necessary to satisfy essential needs, this situation generates a high cost in social terms.